Fractalkine Is Linked to the Necrosome Pathway in Acute Pulmonary Inflammation - Ngamsri, Kristian-Christos; Gamper-Tsigaras, Jutta; Reutershan, Jörg; Konrad, Franziska M. (Frontiers in Medicine, 2021)
Acute pulmonary inflammation affects over 10% of intensive care unit (ICU) patients and is associated with high mortality. Fractalkine (CX3CL1) and its receptor, CX3CR1, have been shown to affect pulmonary inflammation, but previous studies have focused on macrophages. In a murine model of acute pulmonary inflammation, we identified inflammatory hallmarks in C57BL/6J and CX3CR1-/- mice. Pulmonary inflammation was significantly enhanced in the CX3CR1-/- animals compared to the C57BL/6J animals, as assessed by microvascular permeability, polymorphonuclear neutrophil (PMN) migration into lung tissue and alveolar space. The CX3CR1-/- mice showed increased levels of apoptotic PMNs in the lungs, and further investigations revealed an increased activation of necrosome-related receptor-interacting serine/threonine-protein kinases 1 (RIPK1), 3 (RIPK3) and mixed-lineage kinase domain-like pseudokinase (MLKL). Phosphorylated MLKL leads to membrane rupture and damage-associated molecular pattern (DAMP) release, which further enhance inflammation. The release of DAMPs was significantly higher in the CX3CR1-/- mice and led to the activation of various cascades, explaining the increased inflammation. RIPK3 and MLKL inhibition improved the inflammatory response in human PMNs in vitro and confirmed our in vivo findings. In conclusion, we linked CX3CL1 to the necrosome complex in pulmonary inflammation and demonstrated a pivotal role of the necrosome complex in human PMNs.